2013
DOI: 10.1111/1759-5436.12041
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Agriculture Development Cooperation in Africa: Narratives and Politics

Abstract: Chinese agriculture engagements are redefining the 'aid' landscape, moving from a paradigm of development assistance to one of development cooperation mixed with investment. China's leadership asserts that this approach 'infuses new life' into South-South cooperation and 'promote[s] the establishment of a fair and rational new international political and economic order' (GOV 2010: 2). Based on a review of documents and interviews with 30 informants, this article explores Chinese discourses, justifications and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…China has helped to promote the development of the agricultural sector in developing countries by providing funds and using agricultural technology to stimulate its agricultural production potential [10]. This can promote economic development and improve the welfare of the people of the host country [19]. Therefore, China's agricultural investment in these countries is in line with the objective needs of economic development in China and developing countries.…”
Section: Reasons For China's Agricultural Fdimentioning
confidence: 99%
See 2 more Smart Citations
“…China has helped to promote the development of the agricultural sector in developing countries by providing funds and using agricultural technology to stimulate its agricultural production potential [10]. This can promote economic development and improve the welfare of the people of the host country [19]. Therefore, China's agricultural investment in these countries is in line with the objective needs of economic development in China and developing countries.…”
Section: Reasons For China's Agricultural Fdimentioning
confidence: 99%
“…Secondly, the inconsistency of agricultural FDI statistics is also an important reason for this controversy. For example, the transactions reported in some studies and databases are not really realized, and the number of unfinished transactions accounts for a large proportion of the statistics [19]. These reasons have led to the media's expansion of the scale of China's agricultural FDI [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the onset of a food price crisis soon after and partly in response to the energy price crisis, many private investors and governments from net food importing countries also reportedly began to increase their control over land resources in Africa to produce staple food crops for their home markets, especially grains such as rice and maize. Many suggested that these investments originated in particular from Asian countries such as China, South Korea, and India and Gulf States (see von Braun and Meinzen-Dick 2009;Hall 2011;Anseeuw et al 2012;Buckley 2013McMichael 2012Woertz 2013;Carmody 2013;Margulis et al 2013). These investment patterns suggest that investors are primarily responding to opportunities within their own home markets.…”
mentioning
confidence: 99%
“…In the past, academic literature on the impact of China on Africa were often analyses based on aggregated trade and investment flows or based on applying a political analysis on the impact of development assistance models. More recently, the literature on the impact of China on Africa has been considered as part of wider South-South cooperation, although there are also specific sectoral impact studies (Alden 2013;Scoones, Cabral and Tugendhat 2013;Chichava et al 2013;Mukwereza 2013;Buckley 2013;Cabral et al 2013;Pierri 2013). A clear gap in the literature is the specific focus on the impact of China on African fragile states and this is the main focus of this article.…”
mentioning
confidence: 99%